A Numerical Study Laminar Forced Convection of Air for In-Line Bundle of Cylinders Crossflow - Tahseen, Tahseen Ahmad; M., Ishak; M. M., Rahman (Asian Network for Scientific Information, 2013)
In the present paper, the numerical analysis is two-dimensional steady state Navier-Stokes equations and the energy equation governing laminar incompressible flow are solved using the finite difference method (FDM) and the technique body fitted coordinates (BFC). The constant heat flux is imposed on the surface of the tubes as the thermal boundary condition. The arrangement is considered in-line tube-banks the transverse ratio (ST/D) and longitudinal pitch-to-diameter ratio (SL/D) of 1.25, 1.75 and 2.25 respectively are also considered. Reynolds numbers of 30, 125 and 200, and Prandtl number are taken as 0.71. The temperature contours, local Nusselt number distributions to the tube surface and mean Nusselt number were analyzed in this paper. It was found of that the strength of the heat transfer between the surface of tubes and the air flow increases with increasing Reynolds number and increasing pitch-to-diameter rate.